Examining the Asymmetric Effects of Renewable Energy Use, Financial Development, and Trade Openness on Economic Growth in D-8 Islamic Countries - Ahmad, Ali Umar; Abubakar, Atiku Muhammad; Senan, Nabil Ahmed Mareai; Gwadabe, Uzairu Muhammad; Mohammed, Badamasi Sani; Muhammad, Maikudi; AL-Yazidi, Abdulrahman Mohammed Hasan; Sani, Bashir Yakubu; Jamiu, Mustapha; Mustapha, Umar Aliyu (International Journal of Energy Economics and Policy, 2024)
This study investigates the asymmetric impacts of financial development, renewable energy consumption, and trade openness on economic growth in D-8 Islamic countries from 1970 to 2022, using advanced panel data techniques. The findings reveal long-run equilibrium relationships, with financial development and trade openness positively affecting gross domestic product (GDP) growth, while renewable energy exhibits an unexpected negative coefficient. The non-linear autoregressive distributed lag estimates uncover asymmetries, with larger GDP contractions from downside shocks in financial development and trade openness. Renewable energy shows growth penalties from negative changes but symmetric upside benefits. The results highlight the importance of well-developed financial systems, strategic renewable investments, and trade integration for sustainable growth. Policymakers should focus on financial reforms, renewable project facilitation, and reducing trade barriers, considering asymmetric impacts. This study contributes novel empirical evidence on asymmetric dynamics among these variables in D-8 countries, extending the literature through recent non-linear panel modeling techniques and demonstrating the merits of accounting for asymmetries. The combination of methods offers a robust and fresh perspective.